Molecular phylogenetic analysis reveals two new species of Discosia from Italy - Li, Wenjing; Liu, Jian-Kui; Bhat, D. Jayarama; Camporesi, Erio; Dai, Dong-Qing; Mortimer, Peter E; Xu, Jian-Chu; Hyde, Kevin D.; Chomnunti, Putarak (Phytotaxa, 2015)
Two fresh collections of Discosia were made from dead leaves of Fagus sylvatica in Italy. As these collections could not be cultured, the fruiting bodies were directly used for sequencing using a Forensic DNA Extraction Kit. Based on analyses of the concatenated internal transcribed spacer regions of the nrDNA operon (ITS) and large subunit rDNA (LSU) gene sequences, as well as morphological characters, the fresh collections are introduced as two new species, namely D. italica and D. fagi. Phylogenetically, these two species are distinct from all other Discosia species. Morphologically, D. italica is somewhat similar with D. fagi, but can be distinguished using dimension of conidiomata and conidiogenous cells. Descriptions and illustrations of the new taxa are provided herein.